(untitled) (International journal of artificial intelligence, 2026)
This article discusses the current issues of developing work culture in the context of globalization and digitalization. The article analyzes the importance of innovative approaches, in particular, training, mentoring programs, digital educational platforms, simulation and certification systems. It also studies the advanced practices used in European countries to form work culture and substantiates the possibilities of adapting them to national conditions. The results of the study draw attention to the important role of work culture in increasing the professional potential of young people, developing innovative thinking, and training competitive personnel.